Delineation of a subsurface stratigraphic setting using 2D seismic data in Buzurgan and Abu Gharp oil fields, south Iraq - Al-Khafaji, Ranya H.A.; Al-Samarrai, Thair T.; Fadhel, Mohammed S. (Iraqi Journal of Science, 2024)
This study focused on determining the stratigraphic phenomena of the sequences of the Kirkuk group, within the Tertiary age, in the study area at the Buzurgan oil field within the Maysan governorate. In addition to various seismic lines from the completed seismic survey of the study region, data from the Buzurgan oil field wells was utilized. The stratigraphic interpretation results showed that the seismic sections of the Kirkuk Group formations are deposited in the form of a sigmoid configuration through the continuous deposition of shallow-shelf carbonates. Periodic rises in sea level led to episodes of deeper-water sedimentation, including shelf and shelf margin facies. Clastic (sandstone) was deposited as the sea receded from the Ghar formation, which represents the alluvial fan in the outer-shelf basin (slop and basin fan), through periods of sea-level (LST) and in a shallow-marine environment, leading to an overlap between sediments and the presence of sand lenses, onlap, and down lap. The current study shows the phase change in reflectors and perfect hydrocarbon indexes. The study detected a stratigraphic trap in the formation’s eastern part and a large lens in the Southeast parts of the study area.